IDENTIFICATION OF WATER INUNDATION USING QUICKBIRD AND ALOS PALSAR SATELLITE IMAGE STUDY CASE: DAYEUHKOLOT SUBDISTRICT, BANDUNG DISTRICT - Prihanggo, Maundri; Darmawan, Sony; Wikantika, Ketut (Badan Informasi Geospasial in Partnership with MAPIN, 2014)
Indonesia was one of many disasterous potential country, more than 70% of natural disaster happened werehidrometeorogical disaster includingflood. Flood is definedas an overflow or inundation that comes from a river or other body of water and causes or threatens damage, any relatively highÂ streamflowÂ overtopping the natural or artificial banks in any reach of a stream. There are 4 regionsin Java Island that havethe highest potention of flood, they are Jakarta Province,Â Merapi Slope Area, Bengawan Solo and Citarum Watershed Area. The purpose of this study is to identify land cover and water inundation of the study area using Quickbird and ALOS PALSAR image. Before classified and analyze the result, image pre-processing has to be generated in Quickbird and ALOS PALSAR image data to rid off thedistorsion from the data. Quickbird Image can be used for land cover identification with generated object based image classification and ALOS PALSAR Image are applied to identify water inundation in flood area using backscatter value deliniation. By 10th September 2013 with only 5 mm, all of the classes were inundated by water at severalvalues. Keywords: water inundation, remote sensing, Quickbird, ALOS PALSAR.ABSTRAKIndonesia merupakan salah satu negara yang memiliki potensi bencana yang cukup tinggi dan lebih dari 70% bencana yang terjadi merupakan bencana hidrometeorologis termasuk banjir. Banjir didefinisikan sebagai luapan atau genangan yang keluar dari sungai atau badan air dan menyebabkan suatu bahaya dan disebabkan oleh fenomena cuaca dan kejadian yang menyebabkan presipitasi berlebihan pada suatu permukaan bumi. Di Pulau Jawa terdapat empat daerah rawan banjir yang mendapat prioritas tinggi yaitu lereng Gunung Merapi, Provinsi Jakarta dan Daerah Aliran Sungai Bengawan Solo serta Daerah Aliran Sungai Citarum. Tujuan dari studi ini adalah melakukan identifikasi tutupan lahan daerah kawasan banjir beserta luasan genangan air pada tiap tutupan lahan dengan memanfaatkan citra Quickbird dan citra ALOS PALSAR. Sebelum dilakukan proses klasifikasi dan analisis citra, proses pra pengolahan data dilakukan pada citra Quickbird dan ALOS PALSAR agar bersih dari kesalahan yang ada. Tutupan lahan akan didapatkan dari citra Quickbird dengan metode klasifikasi object based dan genangan air diperoleh dengan deliniasi nilai backscatter citra ALOS PALSAR. Dengan curah hujan 5 mm pada tanggal 10 September 2007 seluruh kelas pada area studi tergenang dengan nilai tertentu.Kata kunci: genangan air, penginderaan jauh, Quickbird, ALOS PALSAR.